Zdolność sił zbrojnych Haszymidzkiego Królestwa Jordanii do zapewnienia bezpieczeństwa państwa - Jarząbek, Jarosław (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2015)
The armed forces of the Hashemite Kingdom of Jordan play a key role in ensuring security of the state. Not only do they accomplish the standard tasks of the armed forces in the field of the country’s defense against external threats. Wardens of the ruling monarchy support also police and other forces in ensuring the state’s internal security. Against the background of other countries in the region, the Jordanian Army is characterized by higher professionalism and level of training. Despite the low defense budget it is relatively well armed. Due to that it is able to accomplish its tasks effectively in an extremely difficult international environment and numerous unsettled internal conflicts
Keywords: Jordania; siły zbrojne; bezpieczeństwo; zagrożenia; wyzwania; potencjał militarny